Relationship between High Sensitivity C-Reactive Protein and Total Testosterone Levels in Male Patients with Stage V Chronic Kidney Disease - Metana Puspitasari; MI. Diah Pramudianti; Yuwono Hadisuparto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
The incidence of decreased total testosterone level increases in stage V CKD patients. Decreased total testosterone levels is influenced by uremia and hemodialysis bioincompatibility through an increase in the inflammatory mediator hs-CRP. Obesity and age are risk factors of CKD incidence which can directly affect testosterone level. This study aimed to analyze the relationship between hs-CRP, serum urea, age, obesity, and hemodialysis duration with decreased total testosterone levels in stage V CKD patients. This observational study with cross-sectional approach was performed are 60 stage V CKD patients treated in Dr. Moewardi General Hospital, Surakarta on November 2020. The data were analyzed with 2x2 table test, followed by multivariate analysis using logistic regression. The examinations of total testosterone and hsRP used ECLIA and immunoturbidimetric assay, respectively. This study obtained 21 (37%) study who experienced a decreased total testosterone level (<3ng/mL). hs-CRP level [PR 3.656 (95% CI: 1.202-11,124; p=0.020)]; obesity [PR 4.156 (95% CI: 1.272-13.581; p=0.015)] and urea [PR 4.474 (95% CI: 1.273-15.728; p=0.015)] significantly associated with decreased total testosterone level of <3 ng/ml. Meanwhile age was not statistically significant (p=0.694) and hemodialysis duration obtained PR <1 and CI 95% < 1 (p=0.018). Therefore in patients with stage V, hs-CRP levels ≥ 0.65 mg/dl, serum urea ≥ 120 mg/dL, and obesity correlate with decreased total testosterone level while age is not associated with decreased total testosterone level. The hemodialysis duration is not a risk factor of decreased total testosterone.